THEORETICAL AND PRACTICAL VIEW OF FINANCIAL REGULATION OF INNOVATIVE ACTIVITIES IN THE CONDITIONS OF WAR IN UKRAINE - Vitalii V. Zіanko; Tetiana D. Nechyporenko (Academy Review, 2025)
Key concepts in the field of innovative research were systematized, and the author’s definition of innovation was formulated as the result of the materialization of an innovative idea into a specific tangible form, characterized by new consumer qualities, the implementation of which involves changing established methods of activity to achieve economic, social, environmental, or other effects. This approach expands the traditional understanding of the concept and allows for a more accurate assessment of innovation activity as a complex, dynamic system of actions and interactions among numerous participants in the innovation process, who conduct research and create various types of innovations. It also enables the development of effective tools to support innovation. Empirical data indicate that the financial regulation system of the innovation sector, which brings together both state and private institutions, serves as an effective catalyst for the quantitative growth of innovative projects and the enhancement of their quality. Through financial instruments such as budgetary funding, tax incentives, loans, and investment programs, state institutions contribute to the rapid commercialization of innovative projects and ensure the sustainable development of the economic ecosystem. Private institutions provide a wide range of support for the development of innovative projects. A set of interrelated factors influencing the effectiveness of financial regulation of the innovation process has been identified, allowing for the assessment of its direction and the selection of management methods that are appropriate to the specifics of the innovation process and the type of innovation. Based on this, a model of financial regulation for innovative activity is proposed, featuring a clearly defined hierarchical structure that includes the following key components: goal and objective setting, strategy development, selection of financial stimulation tools, and monitoring of their effectiveness. This approach ensures the systematic and efficient financial regulation of innovations. The analysis of international rankings (GII, IPO, GSEI) indicates that Ukraine has the potential for innovative development. However, the current financial support mechanisms do not ensure adequate access to funding for innovative projects. According to the Global Innovation Index, Ukraine significantly lags behind European countries due to imperfect legislation, insufficient funding for scientific research, and a weak innovation infrastructure. A set of interconnected issues has been identified that pose major obstacles to national innovation development. These include inadequate funding for science, ineffective state innovation policy, an underdeveloped venture capital market, an unfavorable tax environment, and weak intellectual property protection. To enhance Ukraine’s innovative potential and strengthen its position in the global market, a number of strategic recommendations are proposed. These include increasing investment in scientific research, optimizing financial mechanisms, creating a favorable business environment, stimulating the commercialization of innovations, and promoting international cooperation. The implementation of these measures will improve the efficiency of budgetary spending, optimize the regulatory environment, and intensify technology transfer. Ultimately, this will drive the country’s sustainable economic development and contribute to improving its global market position.